MEMBANGUN BUDAYA HUKUM ANTI KORUPSI - ROHMAN, FADHIL IBNU ROHMAN; Syah, Aditya Thaariq; Prabu Alqadar Jayadihati (DE’RECHTSSTAAT, 2023)
Corrupt behavior continues even though the government has issued so many regulations and policies to prevent corruption, even with the threat of very severe legal sanctions, incident after incident of corruption does not seem to end. The purpose of this study is to find out the factors that cause the rise of corruption cases in Indonesia, to find out the influence of law on law enforcement on corruption in Indonesia, and finally to find out the government’s efforts to build an anti-corruption legal culture. Results: Corruption eradication policies in Indonesia are based on three elements in the legal system, namely legal substance, legal structure and legal culture. Legal substance is a set of legal regulations that regulate the eradication of corruption while the legal structure includes institutions involved in law enforcement against criminal acts of corruption. Indonesia already has sufficient legal rules and law enforcement to eradicate corruption, but the problem lies in the commitment to upholding the law.